EMIC waves observed by the low‐altitude satellite DEMETER during the November 2004 magnetic storm. Issue 7 (20th July 2015) - Píša, D.; Parrot, M.; Santolík, O.; Menietti, J. D.
Abstract This paper presents an analysis of ULF (0–20 Hz) waves observed by the low‐altitude satellite Detection of Electro‐Magnetic Emissions Transmitted from Earthquake Regions (DEMETER) during the magnetic storm of November 2004. Since these ULF waves are measured by both electric and magnetic antennas, they may be identified as electromagnetic ion cyclotron (EMIC) waves. While EMIC waves have been previously observed in the low‐altitude ionosphere, this is the first time that they are observed for such extensive time periods and at such high frequencies. A common feature of these emissions is that their observation region in the low‐altitude ionosphere extends continuously from the high‐latitude southern trough in one side up to the high‐latitude northern trough. The analysis of wave propagation points to the possible source region placed in the inner magnetosphere (L ∼ 2–3). Observed wave frequencies indicate that waves must be generated much farther from the Earth compared to the satellite orbit. Exceptionally high frequencies of about 10 Hz can be explained by the source region placed in the deep inner magnetosphere at L ∼ 2.5. We hypothesize that these waves are generated below the local helium gyrofrequency and propagate over a large range of wave normal angles to reach low altitudes at L ∼ 1.11. In order to investigate this scenario, a future study based on ray tracing simulations will be necessary.